A New Development Model for Traditional Craft Villages in Urban Fringes: A Case Study in Ho Chi Minh City, Vietnam - Le-Minh Ngo; Trinh Duy Anh (Journal of Regional and City Planning, 2021)
Experiencing the impacts of rapid urbanization, industrialization and modernization, traditional villages of many Asian cities face the risk of encroachment or function changes. Besides providing jobs for people in their region, traditional craft villages also bring work opportunities for migrants, materials providers, salespeople, and other ancillary service providers. In the rapid process of urban sprawl, many traditional craft villages in peri-urban areas that capture heritage values are gradually shrinking and in danger of disappearing. Therefore, an urgent concern is how to protect traditional villages and traditional residential areas threatened by urbanization. Ho Chi Minh City is a large metropolis engaged in economic, financial, trading, modern industrial, and service activities. There are still many handicraft activities in Ho Chi Minh City, especially traditional occupations, with more than 60 handicrafts distributed over 19 trade villages. Many traditional villages have been encroached and demolished to make place for new developments as a result of speedy urbanization. This paper reports a qualitative study using a mixed method, which includes literature review and comparison, mapping and observation. Based on analyzing the current situation of traditional craft villages and identifying the advantages and disadvantages of two craft village models, this paper proposes a new development model for craft villages in the urban fringes of Ho Chi Minh City.   Abstrak. Mengalami dampak urbanisasi yang cepat, industrialisasi, dan modernisasi, desa-desa tradisional di banyak kota di Asia menghadapi risiko perambahan atau perubahan fungsi. Selain menyediakan lapangan kerja bagi masyarakat di suatu daerah, perkampungan kerajinan tradisional juga membuka peluang kerja bagi para pendatang, penyedia bahan, tenaga penjual, dan tenaga kerja dari jasa lain. Dalam proses urban sprawl yang pesat, banyak desa kerajinan tradisional di pinggiran kota yang menyimpan nilai-nilai heritage secara bertahap menyusut dan terancam punah. Oleh karena itu, yang menjadi perhatian mendesak adalah bagaimana melindungi desa adat dan kawasan permukiman tradisional yang terancam urbanisasi? Kota Ho Chi Minh adalah kota metropolis besar yang terlibat dengan kegiatan ekonomi, keuangan, perdagangan, industri modern, dan jasa. Masih banyak kegiatan kerajinan tangan di Kota Ho Chi Minh, terutama pekerjaan tradisional, dengan lebih dari 60 kerajinan tangan didistribusikan di 19 desa perdagangan. Banyak desa tradisional telah dirambah dan dihancurkan untuk pembangunan baru akibat urbanisasi yang cepat. Makalah ini diselesaikan dengan studi kualitatif dengan menggunakan metode campuran, termasuk tinjauan pustaka dan perbandingan, pemetaan dan observasi. Berdasarkan analisis situasi desa kerajinan tradisional saat ini, mengidentifikasi kelebihan dan kekurangan dari kedua model desa kerajinan, studi ini mengusulkan model pengembangan baru untuk desa kerajinan di pinggiran kota Kota Ho Chi Minh.   Kata kunci. model pembangunan baru, desa kerajinan tradisional, urbanisasi, pinggiran kota, Kota Ho Chi Minh.